Acute cocoa flavanol supplementation improves muscle macro- and microvascular but not anabolic responses to amino acids in older men - Phillips, Bethan E.; Atherton, Philip J.; Varadhan, Krishna; Limb, Marie C.; Williams, John P.; Smith, Kenneth (NRC Research Press, 2016)
The anabolic effects of nutrition on skeletal muscle may depend on adequate skeletal muscle perfusion, which is impaired in older people. Cocoa flavanols have been shown to improve flow-mediated dilation, an established measure of endothelial function. However, their effect on muscle microvascular blood flow is currently unknown. Therefore, the objective of this study was to explore links between the consumption of cocoa flavanols, muscle microvascular blood flow and muscle protein synthesis (MPS) in response to nutrition in older men. To achieve this objective leg blood flow (LBF), muscle microvascular blood volume (MBV) and MPS were measured under postabsorptive and postprandial (I.V glamin, dextrose to sustain glucose ~7.5 mmol·l-1) conditions in 20 older men. Ten of these men were studied with no cocoa flavanol intervention and a further 10 were studied with the addition of 350 mg of cocoa flavanols at the same time as nutrition began. Leg [femoral artery] blood flow was measured by Doppler ultrasound, muscle MBV by contrast-enhanced ultrasound (CEUS) using DefinityTM perflutren contrast agent and MPS using [1, 2-13C2] leucine tracer techniques. Our results show that although older individuals do not show an increase in LBF or MBV in response to feeding, these absent responses are apparent when cocoa flavanols are given acutely with nutrition. However this restoration in vascular responsiveness is not associated with improved MPS responses to nutrition. We conclude that acute cocoa flavanol supplementation improves muscle macro- and microvascular responses to nutrition, independently of modifying muscle protein anabolism.